PERILAKU KONSUMEN SAWI (Brassica Juncea L) PADA BEBERAPA PASAR TRADISIONAL DI KOTA KUPANG PROVINSI NUSA TENGGARA TIMUR - Veby Kadji; Damianus Adar; Maximiliam M. J. Kapa (Undana Press, 2020)
This research has been carried out in the Oeba Traditional Market and Naikoten Traditional Inpres market in October to November 2017. The aim is to find out: (1) Purchase Volume of Mustard Consumer; (2) the preferred type of mustard; (3) identify the factors that influence the demand of mustard consumers; (4) Mustard Sales Volume. The method used in this research is survey. Determination of the location of research carried out by purposive sampling. Respondents were determined as many as 120 people. The type of data collected is primary data and secondary data. To answer the first and fourth objectives, the data were analyzed descriptively qualitatively, answering the second goal using a Likert scale and the third objective of the data analyzed using multiple linear regression. The results showed that; (1) Of the 5 types of mustard the lowest purchase volume is dominated by curly mustard, namely the frequency of purchases per week 1-2 times with a volume of 1 kg - 2 kg. (2) The results of the study of 60 respondents, namely: 30 respondents in traditional traditional markets in Naikoten and 30 respondents in traditional Oeba markets, there are 3 types of mustard which are included in the Average category, namely curly mustard greens, and white mustard, and 2 types of mustard which are included in Like categories namely: mustard huma, and mustard caisim. (3) together - all factors significantly influence the demand for mustard greens shown by the F-count (14.895)> F-table (2.54) is significant at α = 5%. While the results shown by t-count which significantly influence α = 5% are Consumer Taste, and Holidays / Holidays. While the price of mustard greens, other vegetable prices, consumer income, the number of family members, the volume of mustard greens prepared by traders does not significantly affect the demand for mustard. (4) The lowest sales volume of mustard is dominated by Curly mustard, that is 9 respondents or 5% who sell with a volume of 22 - 42Kg / week